Regulation of macroautophagy in amiodarone‐induced pulmonary fibrosis. (3rd June 2015) - Mahavadi, Poornima; Knudsen, Lars; Venkatesan, Shalini; Henneke, Ingrid; Hegermann, Jan; Wrede, Christoph; Ochs, Matthias; Ahuja, Saket; Chillappagari, Shashi; Ruppert, Clemens; Seeger, Werner; Korfei, Martina; et al.
Abstract Amiodarone (AD) is an iodinated benzofuran derivative, especially known for its antiarrhythmic properties. It exerts serious side‐effects even in patients receiving low doses. AD is well‐known to induce apoptosis of type II alveolar epithelial cells (AECII), a mechanism that has been suggested to play an important role in AD‐induced lung fibrosis. The precise molecular mechanisms underlying this disease are, however, still unclear. Because of its amphiphilic nature, AD becomes enriched in the lysosomal compartments, affecting the general functions of these organelles. Hence, in this study, we aimed to assess the role of autophagy, a lysosome‐dependent homeostasis mechanism, in driving AECII apoptosis in response to AD. In vitro, AD‐treated MLE12 and primary AECII cells showed increased proSP‐C and LC3B positive vacuolar structures and underwent LC3B‐dependent apoptosis. In addition, AD‐induced autophagosome‐lysosome fusion and increased autophagy flux were observed. In vivo, in C57BL/6 mice, LC3B was localised at the limiting membrane of lamellar bodies, which were closely connected to the autophagosomal structures in AECIIs. Our data suggest that AD causes activation of macroautophagy in AECIIs and extensive autophagy‐dependent apoptosis of alveolar epithelial cells. Targeting the autophagy pathway may therefore represent an attractive treatment modality in AD‐induced lung fibrosis.